Against the right to revoke citizenship. Issue 8 (17th November 2018) - Carey, Brian
ABSTRACT: The state's right to denationalise and deport certain citizens has been defended in public discourse primarily on the grounds that it is a necessary and proportionate response to certain types of threats to national security. While political theorists have been highly critical of such justifications, less attention has been paid to a second line of defence that is sometimes invoked alongside appeals to national security. According to this view, certain types of behaviour constitute voluntary renunciation of a person's citizenship status, to which denationalisation and deportation is an appropriate response. If successful, this approach would avoid criticisms grounded in the apparent disproportionate, ineffective or inegalitarian nature of citizenship revocation. In this article, I examine (and ultimately reject) the idea that denationalisation and deportation can be an appropriate response to certain types of behaviour. I argue that acts of serious political violence do not amount to voluntary self-exclusion from the political community and that even if they did, denationalisation and deportation would not constitute a fitting response.